A method to estimate the jacking force for pipe jacking in sandy soils - Ji, Xinbo (2021)
Pipe jacking is a commonly used trenchless technology to install pipelines especially in congested urban areas or river crossings. However, the estimation of the jacking force is often heavily dependent on empirical calculations. The jacking force needs to be greater than the combined frictional resistance and face resistance. This investigation proposes to use a modified Protodyakonov's arch model to compute the face resistance. A series of direct shear tests is performed to provide data of interface friction coefficient between different types of soil and pipe. The influence of slurry lubricant is also considered. A two-dimensional plane strain numerical model is conducted, where the surrounding soil is simulated as discrete particles and the lining is simplified as a single big particle. The novel modeling technique enables the evaluation of the normal force acting on the pipe. The friction resistance is then determined by multiplying the interface friction coefficient by the normal force. A ‘wavy’ shaped pipeline model is proposed to define an angular deviation influence factor to scale up the calculated jacking force due to pipe misalignment. In the end, comparison between calculated and field measured jacking force is conducted for three different drives in a pipe jacking project to illustrate the effectiveness of the proposed analysis framework.